KINERJA DAN DISPOSISI MATEMATIS SISWA MELALUI PENERAPAN MODEL PROJECT BASED LEARNING DI SMP - Rosnawati; Rahmah Johar; Zainal Abidin (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2020)
Performance requires students to be actively involved in completing the task, because it is considered not only the products, but the more important is the skill to finish the task. The other important thing to consider in developing a student's performance is a mathematical disposition. Project Based Learning (PjBL) is a technique to make sure students become productive, since they will be working in a project learning activities that makes it more interesting and real so that students are able to develop mathematical performance and disposition. This study aims to analyze the development of the student's performance in completing the task groups and individuals as well as the disposition of its mathematical through the application of the model PjBL. The data were collected through observation, interviews and questionnaires. Research result, it is known that 1) student develops their performance in completing a task group to carry out all stages of the completion of the task. 2) Student develops their performance in completing individual tasks to carry out all stages of the completion of the task. 3) Student’s mathematical disposition after learning with PjBL experiencing growth than before the application of the model, particularly on indicators of interest and curiosity. Abstrak Kinerja menuntut siswa aktif dalam menyelesaikan tugas, karena yang dinilai bukan hanya produk yang dihasilkan, tetapi lebih dipentingkan keterampilan yang dimiliki dalam menyelesaikannya. Hal penting yang harus diperhatikan dalam mengembangkan kinerja adalah disposisi matematis siswa. Model Project Based Learning (PjBL) membuat siswa menjadi produktif, karena mereka akan bekerja dalam sebuah proyek yang aktivitas belajarnya lebih menarik dan nyata sehingga siswa mampu mengembangkan kinerja dan disposisi matematisnya. Penelitian ini bertujuan untuk menganalisis perkembangan kinerja siswa dalam menyelesaikan tugas kelompok dan individu serta disposisi matematisnya melalui penerapan model PjBL. Teknik pengumpulan datanya dengan observasi, wawancara dan angket. Hasil penelitian, diketahui bahwa 1) siswa mengembangkan kinerjanya dalam menyelesaikan tugas kelompok dengan melaksanakan seluruh tahap penyelesaian tugas. 2) siswa mengembangkan kinerjanya dalam menyelesaikan tugas individu dengan melaksanakan seluruh tahap penyelesaian tugas. 3) disposisi matematis siswa sesudah pembelajaran dengan model PjBL mengalami perkembangan dibandingkan sebelum penerapan model tersebut, terutama pada indikator minat dan keingintahuan. Kata Kunci: Project Based Learning, Kinerja, Disposisi Matematis